PENGEMBANGAN BIODEGRADABLE BOX (BIOBOX) DARI TEPUNG TALAS DAN LIMBAH KULIT KACANG TANAH - Salma Fadilla Nur Safitri; Ivan Fauzan Pratama; Kirana Shalsabilla Yusuf; Diana Putri Lestari; Nindya Tri Muliawati; Faris Hermawan (University of Bengkulu, 2026)
[Development of Biodegradable Box from Taro Flour and Peanut Shell Waste] Biobox is an environmentally friendly packaging innovation developed from taro flour and peanut shell waste as an alternative to Styrofoam. This innovation comes as a solution to environmental problems due to disposable packaging waste that is difficult to decompose. Taro flour serves as a natural polymer that forms the basic structure of the packaging, while peanut shells act as a source of cellulose. The Biobox manufacturing process involves sample preparation with the addition of 10% NaOH, pulping, molding and drying. The resulting biobox has brownish physical properties, a slightly rough surface, a water absorption value of 2.53% and a decomposition capacity of 60.35%. Characterization results using FTIR (Fourier Transform Infrared) Spectroscopy effectively show the presence and interaction of the main functional groups of each component forming this biopolymer-based Biobox. Keywords: Biobox; Cellulose; Packaging; Peanut Shell Waste; Taro Flour.